Alterations in peripheral CD4+ T cell subsets and their association with metabolic markers in obese children - Saito, Reiko; Hirakawa, Jun; Kuwamura, Mami; Hoshina, Takayuki (Frontiers in Endocrinology, 2025)
IntroductionChildhood obesity may elevate the risk for adult obesity because of chronic inflammation and immune dysregulation; however, studies on the immune system in obese children are limited. This study aimed to investigate peripheral blood lymphocyte subpopulations in obese children and their association with metabolic markers.MethodsThis prospective study included 30 obese children (median age: 11.5 years) and 22 age-matched non-obese controls. Lymphocyte populations were compared between the two groups. Additionally, factors influencing these populations were assessed in the obese group.ResultsThe proportion of CD4+ T cells and the ratio of naïve to memory CD4+ T cells were significantly lower in obese children than in non-obese children (P = 0.006 and P = 0.035, respectively). Regulatory T (Treg) cell counts were significantly higher in obese children than in non-obese children (P = 0.049). The proportion of CD4+ memory T cells positively correlated with serum alanine aminotransferase levels. The proportion of Tregs was negatively correlated with serum insulin levels and positively correlated with blood glucose levels. The number of CD4+ T cells and the ratio of naïve to memory CD4+ T cells were lower in obese children with a disease duration of <5 years compared to that in non-obese children. However, obese children with a disease duration of ≥5 years had a high number of CD4+ T cells.ConclusionsThis study highlights the impact of childhood obesity on immune dysregulation. The changes in T cell subpopulations in obese children differ from those observed in obese adults and vary depend on the duration of obesity.